Hypo osmotic swelling test of caprine epididymal sperms - SWAIN, DILIP KUMAR; SWARNKAR, PRASANT; YADAV, SARVAJEET (The Indian Journal of Animal Sciences, 2012)
The study was designed to find a suitable HOS solution concentration for the sperms retrieved from 3 segments of epididymis. The major aim of the study was to evaluate the pattern of osmotic resistance of the epididymal sperms to different concentrations of hypo-osmotic solutions. We reported the highest sperm coiling at 75 mOsm/L for the caput and corpus sperms whereas cauda sperms exhibited highest coiling at 125mOsm/L. The osmotic resistance of the cauda sperms was greater than that of the caput and corpus. Further studies are required to study the exact mechanism behind the sperm membrane integrity and its relationship with the epididymal transit and how the osmotic resitance of the sperms gradually increased during the epididymal transit.